The Economic and Social Effects of Zamindari Abolition in Andhra - Planning Commission (Planning Commission, 1963)
The existence of different systems of land tenure in a country, with differences in regard to the nature of the relationship between the Government or other tax collecting authorities on the one hand and the notes on the other hand, and in regard to their respective rights and obligations, raises vital questions of agricultural efficiency and social justice. If the burdens imposed ultimately on the ryots and the incentives provided to them for improving their agriculture under one system of tenure are substantially different from the same under another system, they give rise to serious problems of inequalities. The two most important systems of land tenure in India which require to be carefully studied in this connection are : (1) the system of permanently settled estates or the zamindari system; (2) and the ryotwari system. These two systems had been also the most important systems prevailing in the Andhra State before the zamindari system was abolished in 1949. The total zamindari area in the Andhra Slate was approximately one-third of the area of the State. The area was, however, mostly concentrated in the Visakhapatnam and Srikakulam districts in the north, the East and West Godavari and Krishna districts, and in the districts of Nellore and Chittur.
The Economic and Social Effects of Zamindari Abolition in Andhra
Planning Commission Library